Magic tree house Merlin missions, #07 night of the new magicians - Osborne, Mary Pope; Murdocca, Sal (Random House New York, 2006)
Jack and Annie visit the Paris World's Fair of 1889 in an effort to protect four scientific pioneers from an evil sorcerer